Part-time Employment and Business Cycle in Central and Eastern Europe - Kamila Fialová (Review of Economic Perspectives, 2017)
This article explores the development of part-time employment in Central and Eastern Europe and compares it to Western Europe. On the macro level it examines the role of the business cycle and its effect on part-time employment in the two groups of countries since 2001. The key result reveals that contrary to the West, the business cycle development exerts a significant negative effect on the part-time employment rate in Eastern Europe. When the economy operates below its potential, part-time employment tends to grow more than full-time employment. This finding is consistent with the labour demand effect and reflects the pursuit of flexibility by firms as well as the adjustment in composition of employment to changing economic conditions. The countercyclical effect is even stronger for involuntary part-time employment. Separate analyses of individual demographic groups of workers reveal a significant negative effect of the business cycle on part-time employment of older workers and male prime-age workers in Eastern Europe. In contrast, the effect is insignificant for young workers and unclear for prime-age women.
Keywords: J08; J21; J22; O52; 330; business cycle; part-time employment; working time